Answer:
whooops no one had answered u from 50 min!
Brian is 3 years old.
Hope this helps!
Answer:
- using the rule given: 2.5
- using an exponential rule: 7
Step-by-step explanation:
Evaluating the linear rule given, for n = 1, we have ...
a1 = 7(1/2)(1) -1 = 7/2 -1 = 5/2 = 2.5
_____
We suspect you may intend the exponential function ...
an = 7(1/2)^(n-1)
Then, for n = 1, we have ...
a1 = 7(1/2)^(1 -1) = 7(1) = 7 . . . . the first term is 7
_____
When writing an exponential expression in plain text, it requires the exponential operator, a caret (^). If the exponent contains any arithmetic, as this one does, it must be enclosed in parentheses.
Answer:
17; 22; 27; 32
the terms increase by 5 each time
17 + 5 = 22 (the second term)
17 + 5 * 2 = 27 (third term)
So to get to the 52nd term, we have to add 5* 51 = 255 to 17
17 + 255 = 272
Step-by-step explanation:
Answer:
x > - 1
Step-by-step explanation:
Given
- 3x - 5 < - 2 ( add 5 to both sides )
- 3x < 3
Divide both sides by - 3, reversing the symbol as a result of dividing by a negative quantity
x > - 1